Immunopathology of anthroponotic cutaneous leishmaniasis and incidental diagnostic tool of metastatic granuloma: A case-control study. (March 2021) - Shamsi Meymandi, Simin; Dabiri, Shahriar; Eslammanesh, Tahereh; Azadeh, Bahram; Nadji, Mehrdad; Shamsi Meymandi, Manzumeh; Dabiri, Bahram; Dabiri, Donya; Hakimi Parizi, Maryam; Bamorovat, Mehdi
Abstract: Background: Cutaneous leishmaniasis (CL) is a neglected disease with important public health concerns in many parts of the world including Iran. Objectives: We aimed to explore the histological changes and immunohistochemical quantification of inflammatory cells and their role in the immunopathology of acute, chronic non-lupoid, and chronic lupoid skin lesions in anthroponotic CL (ACL). Methods: In this study, skin biopsies of 53 patients with ACL were taken. Samples were studied by light microscopy and immunohistochemistry to quantify the immune and inflammatory cells. Results: Of the 53 skin lesions, 38 were acute, nine chronic non-lupoid and six chronic lupoid. CD68 + macrophages were the most common cells. CD3 + T-lymphocytes were present as diffuse and focal dermal infiltrates and CD8 + cytotoxic T-lymphocytes were the dominant lymphocyte type, constituting more than 50% of the lymphocyte population. CD4 + T-lymphocytes in chronic non-lupoid (10.57 ± 2.37%) and chronic lupoid (14.40 ± 1.28%) lesions were more than those observed in the acute form (8.61 ± 1.31%), but the differences were not statistically significant. CD20 + B-lymphocytes constituted a small percentage of inflammatory cell infiltrates. CD1a + Langerhans cells showed progressively higher percentages from acute to chronic non-lupoid to chronic lupoid lesions. The differences were statistically significant (P < 0.05) between acute and chronic lupoid lesions. CD68 + macrophages were the most common cells and CD8 + T lymphocytes remained the predominant T-lymphocytes in acute, chronic non-lupoid, and chronic lupoid lesions, suggesting their central role in the pathogenesis and possible healing of CL. Conclusion: Focusing on the deep dermis, periadnexal and/or peripheral margins or even papillary tip of inflammatory sites of sandfly bites, we sometimes find granuloma inside lymphatic vessels (lymphangiectatic metastatic granuloma) or even infected macrophages with engulfed Leishman bodies faraway. Knowledge of the histopathological and immunohistochemical findings for various forms of ACL is essential in improving clinical and medical strategies and crucial for proper prophylactic and therapeutic plans. Highlights: Cutaneous leishmaniasis is a neglected disease with important public health concerns. Biopsies of ACL patients were studied to quantify the immune and inflammatory cells. Of the 53 skin lesions, 38 were acute, nine chronic non-lupoid and six chronic lupoid. CD68+ macrophages were the most common cells. Knowledge of the various forms of ACL is essential in improving medical strategies.